(3JTZjd GdGLgRI GdJYdjejI (B/s - (3CfOQGhS, JjSjQs ((3GdCQOf (B:s (3OGQ GdCed ddfTQ h GdJhRjY ,s, 1999)
(3Gf GdJYGed eY GdCLgRI GdJYdjejI GdSeYjI h GdHUQjI dGSdhH gGOa jMfe GdeJYdejf OGFeG GdJYQa Ydi gPg GdCLgRI h GdEMGWI HgG Yf cJH h JUfjagG ef MjK GdMhGS GdJj SJNGWHgG h GdNHQGJ GdJj SJghjgG h HGdJGdj cjajI JTZjdgG JegjO dGSJNOGegG h JhXjagG aj GdehGba GdJYdjejI h Ydjg aGf eMJhjGJ gPG GdcJGH JTZjd GdGLgRI GdJYdjejI JTcd aj eLehYgG GVGaI fhYjI debQQGJ JNUU GdecJHGJ h JcfhdhLjG GdJYdje GdJj GYJeOJgG LGeYI GdHdbGA GdJWHjbjI aj GdcdjGJ GdLGeYjI GdehSWI GdJGHYI dgGs
Keywords: (3GdSeYj GdHUQjs; (3JcfhdhLjG GdJYdjes